Simulation on the molecular radiosensitization effect of gold nanoparticles in cells irradiated by x-rays. (30th July 2015) - Xie, W Z; Friedland, W; Li, W B; Li, C Y; Oeh, U; Qiu, R; Li, J L; Hoeschen, C
Abstract: Abundant studies have focused on the radiosensitization effect of gold nanoparticles (GNPs) in the cellular environment with x-ray irradiation. To better understand the physical foundation and to initially study the molecular radiosensitization effect within the nucleus, a simple cell model with detailed DNA structure in the central nucleus was set up and complemented with different distributions of single and multiple GNPs in this work. With the biophysical Monte Carlo simulation code PARTRAC, the radiosensitization effects on both physical quantities and primary biological responses (DNA strand breaks) were simulated. The ratios of results under situations with GNPs compared to those without GNPs were defined as the enhancement factors (EFs). The simulation results show that the presence of GNP can cause a notable enhancement effect on the energy deposition within a few micrometers from the border of GNP. The greatest upshot appears around the border and is mostly dominated by Auger electrons. The enhancement effect on the DNA strand breakage becomes smaller because of the DNA distribution inside the nucleus, and the corresponding EFs are between 1 and 1.5. In the present simulation, multiple GNPs on the nucleus surface, the 60 kVp x-ray spectrum and the diameter of 100 nm are relatively more effective conditions for both physical and biological radiosensitization effects. These results preliminarily indicate that GNP can be a good radiosensitizer in x-ray radiotherapy. Nevertheless, further biological responses (repair process, cell survival, etc) need to be studied to give more accurate evaluation and practical proposal on GNP's application in clinical treatment.